2003
DOI: 10.1034/j.1600-0765.2003.00663.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in gingival crevicular fluid matrix metalloproteinase‐8 levels during periodontal treatment and maintenance

Abstract: In conclusion, clinical improvement following SRP was associated with significant reductions in MMP-8 levels. The GCF concentration of MMP-8 decreased after initial therapy but reduced even more dramatically (approximately 50%) following a 3-month period of maintenance (P < 0.001).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
86
1
6

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(102 citation statements)
references
References 31 publications
(45 reference statements)
9
86
1
6
Order By: Relevance
“…For instance, Ince et al [22] reported a reduction of matrix metalloproteinase-8 (MMP-8) levels in the gingival crevicular fluid in chronic periodontitis after probiotic treatment. Active MMP-8 is the main host cell-derived collagenase that leads to periodontal tissue destruction and it is mostly found in sites with progressive periodontitis [54]. An increased level of tissue inhibitor of metalloproteinases-1 (TIMP-1), which has inhibitory effect against all MMPs, was also noted in patients treated with probiotic [22].…”
Section: Discussionmentioning
confidence: 95%
“…For instance, Ince et al [22] reported a reduction of matrix metalloproteinase-8 (MMP-8) levels in the gingival crevicular fluid in chronic periodontitis after probiotic treatment. Active MMP-8 is the main host cell-derived collagenase that leads to periodontal tissue destruction and it is mostly found in sites with progressive periodontitis [54]. An increased level of tissue inhibitor of metalloproteinases-1 (TIMP-1), which has inhibitory effect against all MMPs, was also noted in patients treated with probiotic [22].…”
Section: Discussionmentioning
confidence: 95%
“…More specifically, the presence of matrix metalloproteinase-8 (MMP-8, an enzyme responsible for tissue destruction) in GCF has been positively associated with periodontitis progression. [59][60][61] In 2010, an immunochromatographic chair-side dipstick test became commercially available to determine the presence or absence of MMP-8 in the GCF with similar precision as conventional laboratory assays. 62 Recently, it has been reported that salivary soluble toll-like receptor-2 and interleukin-4 correlate positively with periodontal disease process.…”
Section: Periodontal Diseasesmentioning
confidence: 99%
“…Diversas MMPs são identificadas em tecidos periodontais (MMP-1, MMP-2, MMP-3, MMP-7, MMP-9, MMP-8, MMP-13, MT-1MMP) (TERVAHARTIALA et al 2000, EJEIL et al 2003, CESAR NETO et al 2004, sendo encontradas em baixos níveis em tecidos normais, e em altas concentrações nos tecidos inflamados (KINANE et al 2003). Dessa forma acredita-se que MMPs e TIMPs estejam envolvidos na remodelação fisiológica dos tecidos periodontais assim como na 21 destruição tecidual vista nas doenças periodontais (REDDY et al 2003).…”
Section: Introductionunclassified
“…A ativação das MMPs é regulada por um grupo de proteínas endógenas chamado de inibidores teciduais de metaloproteases (TIMPs), capazes de inibir praticamente todos os membros da família das MMPs de forma não específica (BAKER 2002). Em condições fisiológicas, os TIMPs estão em balanço com as MMPs, sendo a matriz extracelular remodelada e forma extremamente controlada.Diversas MMPs são identificadas em tecidos periodontais (MMP-1, MMP-2, MMP-3, MMP-7, MMP-9, MMP-8, MMP-13, MT-1MMP) (TERVAHARTIALA et al 2000, EJEIL et al 2003, CESAR NETO et al 2004, sendo encontradas em baixos níveis em tecidos normais, e em altas concentrações nos tecidos inflamados (KINANE et al 2003). Dessa forma acredita-se que MMPs e TIMPs estejam envolvidos na remodelação fisiológica dos tecidos periodontais assim como na 21 destruição tecidual vista nas doenças periodontais (REDDY et al 2003).…”
unclassified